Rebranding Politik dan Makna Simbolik: Analisis Semiotika Perubahan Logo Partai Solidaritas Indonesia dari Mawar ke Gajah - Reza Mehdi Fauzi; Sigit Andrianto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study analyzes the transformation of political identity in Indonesia's contemporary democratic era, specifically how new political parties such as the Partai Solidaritas Indonesia (PSI) strategically adapt to maintain relevance and expand their support base through symbolic rebranding. The phenomenon of the PSI's symbol change from a red rose to an elephant captured the author's attention because it reflects the complexity of modern political communication, which involves not only visual aspects but also profound semiotic, psychological, and sociological dimensions. This research uses a qualitative approach with Roland Barthes' semiotic analysis. The aim of this research is to uncovers the meaning behind this symbolic transformation, from the party's strategic motivations, the rebranding implementation process, to its impact on public perception and PSI's political positioning within the Indonesian political landscape. Political rebranding, involving the intersection of communication theory, political science, semiotics, and cultural studies, is relevant and contributes to the development of academic literature on political branding in Indonesia. This research can provide new perspectives on the dynamics of contemporary political communication and serve as a reference for political practitioners, academics, and the general public interested in understanding how symbols and visual identities play a role in the construction of political meaning in the digital era. It also opens up space for further discussion on the effectiveness of rebranding strategies in the context of Indonesia's multiparty and democratic politics.